A study of Discourse in Teaching English in English classroom - Dulal, Ganesh Prasad (Medha: A Multidisciplinary Journal, 2025)
This study was aimed to explore a classroom discourse and  uses for the teaching of English as a FL/SL. To achieve the purpose, the researcher made a classroom observation as a tool of data collection. The class was randomly selected from B.Ed first year in the academic session 2081 B. S. of Mahendra Morang   Adarsha Multiple Campus, Biratnagar. After having simply the record, transcription was made. Based on the transcription, among the model of classroom discourse, the Sinclair and Coulthard (1975) model was selected as a sign post of this classroom based discourse analysis. Comparing the model with the actual classroom transcription, the discourse analysis was made and the interpretation and recommendation were finally put in the study. Based on the analysis it was confirmed that the classroom from which the data in the paper was taken didn’t promote equal roles for teacher and students. Teacher was dominating the class and students were not fully participating in the classroom. Additionally, there was unequal amount of moves and exchanges between teacher and students. All the moves, acts and exchanges between them were unequal amount of moves and exchanges between teacher and students. All the moves, acts and exchanges between them were unequal. The class was teacher dominated. The initiation was from the teacher. There was no room for students to begin or initiate the conversation. When we see the lines from the transcription, teachers talk is about 10 lines more than that of students talk. Finally, it was recommended that teachers should give sufficient time for their students to make them practice the language and students are also needed to fully participate in the classroom in English lessons.